17+8 Tuntutan Rakyat: Kajian Hukum atas Gerakan Sosial dan Partisipasi Politik Generasi Milenial-Gen Z dalam Menyuarakan Hak Konstitusional - Patabang, Viktor (CV. Kurnia Grup, 2025)
The wave of demonstrations that occurred in Indonesia during the August-September 2025 period marked a new era of digital activism that successfully mobilized masses on a massive scale. This article analyzes the social movement phenomenon initiated by millennials and Gen Z through social media platforms using hashtags #IndonesiaGelap (Indonesia Dark) and #ResetIndonesia. These demonstrations carried 17+8 people's demands encompassing various crucial issues ranging from political reform, government transparency, to socio-economic justice. This research explores how public figures from the content creator and influencer circles, such as Jerome Polin and Andovi da Lopez, served as catalysts for mass mobilization, transforming the conventional social movement paradigm into hybrid activism that combines digital power with on-ground action. Through a qualitative approach utilizing social media content analysis and field documentation, this article reveals the dynamics of cross-generational participation—students, workers, to online motorcycle taxi drivers—united in one voice demanding change.